A reliability assessment software using Kinect to complement the clinical evaluation of Parkinson's disease (2015)
Parkinson's disease is characterized by alterations in the gait pattern that may increase the risk of falls. Variations in the gait pattern cannot be objectively measured in clinical examination, so it is necessary to adapt devices to measure objectively, valid and replicable changes in gait patterns that are part of the evolution of the disease and / or pharmacotherapy. In an interdisciplinary effort, we developed the 'e-Motion Capture System' software, which is able to calculate motor (cadence, stride and step length) and spatiotemporal (velocity and acceleration) parameters that affect quality of life in patients with Parkinson's disease.